External and internal Load and their Effects on Professional Volleyball Training - Lima, Ricardo Franco; Silva, Ana; Afonso, José; Castro, Henrique; Clemente, Filipe Manuel (International Journal of Sports Medicine, 2020)
The purpose of this study was twofold: (i) characterize the external and internal training load of professional volleyball players with a focus on intra-week changes and (ii) test the relationships between internal and external load measures. Eight male professional players (age: 23.0±5.22 yo; body mass: 84.5 ± 7.58 kg; height: 193.0±9.71 cm; BMI: 22.0±0.02 kg/m2) were monitored daily over 15 weeks. The monitoring process included both internal (rate of perceived exertion [RPE] and session-RPE [s-RPE]) and external load variables, which were measured by an inertial measurement unit. Results revealed that, within-week variations revealed that RPE was significantly higher during MD-2 (d=0.59) and MD-3 (d=0.56) than MD-1. A significantly higher number of jumps was observed on MD-2 than MD-1 (d=0.69). Considering the relationships between internal and external load measures, small positive correlations were found between RPE and the number of jumps (r=0.17) and between s-RPE and the number of jumps (r=0.49). In conclusion, a tapering strategy was observed on the day before a match, as internal and external loads decreased. Both internal and external load measures are necessary to provide an accurate perception of the impact of training stimuli on players.
Keywords: training load monitoring; load quantification; sports training; performance analysis; internal and external load